1997
DOI: 10.1002/(sici)1099-1573(199706)11:4<281::aid-ptr281>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory and antibacterial activities of C-methylflavonols fromPiliostigma thonningii

Abstract: Newly described C‐methylflavonols, 6,8‐di‐C‐methylquercetin 3‐methyl ether, 6‐C‐methylquercetin 3,7‐dimethyl ether, 6,8‐di‐C‐methylquercetin 3,7‐dimethyl ether together with the known compounds quercetin, quercitrin, 6‐C‐methylquercetin 3‐methyl ether, 6‐C‐methylquercetin 3,7,3′‐trimethyl ether, 6,8‐di‐C‐methyl‐ kaempferol 3‐methyl ether and 6,8‐di‐C‐methylkaempferol 3,7‐dimethyl ether isolated from the leaves of Piliostigma thonningii, were tested for their ability to inhibit prostaglandin synthesis in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 9 publications
2
26
0
1
Order By: Relevance
“…In vivo anti-inflammatory and antibacterial activity; C-methylflavonols (Ibewuike et al, 1997;Olakunle, 2011). Antibacterial activity; antihelmintic activity (Akinpelu and Obuotor, 2000) Leaves chewed to cure stomach pains in East Africa (Kokwaro, 1993).…”
Section: Piliostigma Thonningiisupporting
confidence: 65%
“…In vivo anti-inflammatory and antibacterial activity; C-methylflavonols (Ibewuike et al, 1997;Olakunle, 2011). Antibacterial activity; antihelmintic activity (Akinpelu and Obuotor, 2000) Leaves chewed to cure stomach pains in East Africa (Kokwaro, 1993).…”
Section: Piliostigma Thonningiisupporting
confidence: 65%
“…Ethnomedically, the bark, root, pod, young stem or leaves have been used for treating leprosy, smallpox, coughs, ulcer, heart pain, gingivitis, snake bite, dysentery, fever, wounds and a variety of closely related disease conditions (Irvine, 1961;Asuzu and Onu, 1994;Bombardelli et al, 1973Bombardelli et al, , 1992Bombardelli et al, , 1994Dalziel, 1937;Watt and Breyer-Brandwijk, 1962;McGaw et al, 1997;Okwute et al, 1986). Previously isolated constituents include flavonoids and proanthocyanidins (Snatzke and Wolff, 1989;Lamikanra et al, 1990;Komiya et al, 1975), labdane derivatives (Hashidoko et al, 1991;Huang et al, 1993), a kaurane diterpene (Roitman and James, 1985;Martin et al, 1997), C-methylflavonols (Breitmeier and Voelter, 1990;Harborne et al, 1994;Rabesa and Voirin, 1985;Voirin, 1983;Aderogba et al, 2003;Rasamoelisendra et al, 1989) and phenoxychromones (Ibewuike et al, 1996(Ibewuike et al, , 1997, while broad phytochemical analysis showed the presence of other classes of constituents such as saponins, tannins and polyphenols (Irvine, 1961;Bombardelli et al, 1994).…”
Section: Introductionmentioning
confidence: 67%
“…Among quercetins some have been shown to exhibit strong lipid peroxidation inhibitory effects and cytotoxicity (Cos et al, 2001) when tested against oral microorganisms. Thus, the present findings on the antimicrobial activities of the C-methylated flavonols and the oxychromonol isolated from P. reticulatum (Ibewuike et al, 1997) lend support to the well founded effectiveness of flavonoids and closely related structures against microbial infections, and hence provide justification for the usage of this plant in folk medicine for the treatment of viral infections, oral sores and inflammations (Iinuma et al, 1994;Kirtikar et al, 1993;Yusuf et al, 1994;Liu et al, 1990).…”
Section: Antimicrobial Activity Testsmentioning
confidence: 99%
“…Most antibacterial activity data concerns aglycones, and only small amounts of data on glycosides can be found (Metsämuuronen and Siren 2014). Out of all these flavonoids, aglycones, quercetin (RiceEvans et al 1996;Ibewuike et al 1997;Puupponen-Pimiä et al 2001), kaempferol (Rauha et al 2000), and myricetin (Puupponen-Pimiä et al 2001) have already been recognized to possess antibacterial activity. However, quercetin-3-glucoside (quercitrin) (PuupponenPimiä et al 2001) has actually been found to be inactive.…”
Section: Antifungal and Antibacterial Activitiesmentioning
confidence: 99%